Molecular-level evaluation of selected periodontal pathogens from subgingival regions in canines and humans with periodontal disease - Gołyńska, Magdalena; Polkowska, Izabela; Bartoszcze-Tomaszewska, Małgorzata; Sobczyńska-Rak, Aleksandra; Matuszewski, Łukasz (Journal of veterinary science (Suwŏn-si, Korea), 2017)
Dogs commonly serve as a model for various human conditions, including periodontal diseases. The aim of this study was to identify the anaerobic bacteria that colonize the subgingival areas in dogs and humans by using rapid real-time polymerase chain reaction (RT-PCR)-based tests and to compare the results obtained in each species. Bacterial microflora evaluations, both quantitative and qualitative, were performed by applying ready-made tests on twelve dogs and twelve humans. Five samples were collected from each subject's deepest gingival pockets and joined to form a collective sample. The results of the study revealed interspecies similarities in the prevalences of ( .) , and . Red complex bacteria comprised the largest portion of the studied bacterial complexes in all study groups, with being the most commonly isolated bacterium. The results show similarities in the prevalence of bacterial microflora in dogs and humans. Microbiological analysis of gingival pockets by using rapid real-time PCR-based tests in clinical practice, both veterinary and human, can facilitate the choice of appropriate pharmacological treatment and can provide a basis for subsequent verification of the treatment's effectiveness.